(untitled) (Research, Society and Development, 2025)
Introduction: Addressing accidents involving sharp materials is essential, as they represent one of the main occupational risks faced by nursing professionals in hospital environments. These incidents expose workers to potentially dangerous biological agents, affecting both their physical integrity and emotional well-being. Their occurrence is linked to various factors such as excessive workload, operational failures, lack of continuous training, and structural and organizational deficiencies, highlighting the need for constant and integrated preventive strategies. Objective: To analyze the protective measures implemented in hospitals by nursing professionals, aiming to prevent accidents involving sharp materials and to promote safer work environments. Methodology: A non-experimental, descriptive research was carried out in the form of an integrative literature review, with searches conducted in the PubMed®, SciELO®, and Google Scholar databases, covering publications from 2021 to 2025. Initially, 56 studies were identified, and 15 were selected after applying inclusion and exclusion criteria. The selected works were subjected to qualitative content analysis and quantitative assessment regarding the number of publications. Conclusion: The results showed that reducing accidents involving sharp materials depends on institutional commitment to biosafety, continuous training programs, effective monitoring of PPE use, compliance with NR-32 protocols, and the consolidation of an organizational culture focused on the care and appreciation of healthcare professionals. Implementing these measures significantly contributes to minimizing occupational risks and improving the safety and quality of care provided.